2011
DOI: 10.1080/13662716.2011.583464
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the French Defence Innovation System: New Roles and Capabilities for the Government Agency for Defence

Abstract: Defence innovation systems are structured around two main groups of players that interact in the development of complex programmes: the state (the client and the government agency) and the systems integrators. Technological and institutional changes since the 1990s have affected the division of labour and knowledge in the industry. In this paper, we show the origins of these changes based on information derived from 45 qualitative interviews conducted between 2000 and 2008, which demonstrate the new capabiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 46 publications
(49 reference statements)
0
19
0
1
Order By: Relevance
“…Knowledge-intensive businesses and R and D services [69] are helpful in providing learning opportunities to NIS [70], in favoring the development of an approach towards innovation [71], and in extending the competitiveness of territorial IS and of the innovation provided to it [72]. Technology is thought of as the process leading to the improvement of knowledge for the entirety of an IS [73], especially if knowledge is recombined and transformed through the output of technology-based activities [74].…”
Section: Technology In Is: Main Research Areasmentioning
confidence: 99%
“…Knowledge-intensive businesses and R and D services [69] are helpful in providing learning opportunities to NIS [70], in favoring the development of an approach towards innovation [71], and in extending the competitiveness of territorial IS and of the innovation provided to it [72]. Technology is thought of as the process leading to the improvement of knowledge for the entirety of an IS [73], especially if knowledge is recombined and transformed through the output of technology-based activities [74].…”
Section: Technology In Is: Main Research Areasmentioning
confidence: 99%
“…National innovation systems are assessed as the totality of institutions and practices that interact to produce and diffuse new technology whereas sectoral and technological innovation systems are concerned with adoption of certain technologies in or across sectoral boundaries [26]. It is suggested that it is the co-evolution of national, sectoral and technological systems that has shaped specialised industries, like defence, and that innovation is driven or stifled by the interactions, inter-linking processes and changes in technology and institutions [27][28][29].…”
Section: Innovation Strategy Within Limited Marketsmentioning
confidence: 99%
“…While the role of firms in the realization of advanced defense research programs has been strengthened, the role of the DGA has been redirected toward following up complex program developments, and more downstream activities related to testing and trialing in the operationalization phases of these programs (Guichard, 2005). Thus, with the exception of the nuclear sector, the interface with scientific research and technological networks is provided by firms (Lazaric et al, 2011). This situation offers possibilities of hitherto unauthorized interaction, based on the creation of complementary assets.…”
Section: New Strategies For Defense Firms: Diversifying Their Randd Andmentioning
confidence: 99%
“…4 For this reason, and at the same time, the Ministry of Defense redefined its priorities: focusing its funding efforts on financing specifically military technologies, and leaving dual technology financing to civil ministries (Mérindol and Versailles, 2010). 5 More generally, we saw the end of the era of large-sale programs (Cohen, 2007), with the role of the General Directorate for Armament (Direction Générale pour l'Armement, DGA) being redefined (Lazaric et al, 2011) and the development of a knowledge distribution policy (to use the distinction introduced by Ergas, 1987) marked by the emergence of new dynamics, such as competitiveness clusters (Brette and Chappoz, 2007). This has resulted in a decentralization of the decision-making process and the key figures within the NIS.…”
Section: Major Impact On Randd Projects Especially For Defense Firmsmentioning
confidence: 99%
See 1 more Smart Citation